2006
DOI: 10.1073/pnas.0609274103
|View full text |Cite
|
Sign up to set email alerts
|

Distant touch hydrodynamic imaging with an artificial lateral line

Abstract: Nearly all underwater vehicles and surface ships today use sonar and vision for imaging and navigation. However, sonar and vision systems face various limitations, e.g., sonar blind zones, dark or murky environments, etc. Evolved over millions of years, fish use the lateral line, a distributed linear array of flow sensing organs, for underwater hydrodynamic imaging and information extraction. We demonstrate here a proof-of-concept artificial lateral line system. It enables a distant touch hydrodynamic imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
155
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(158 citation statements)
references
References 31 publications
1
155
0
2
Order By: Relevance
“…Modelling the pressure sensing after natural or artificial devices (Fan et al 2002;Coombs & Braun 2003;Yang et al 2006), we assume a finite noise-tosignal ratio g in that measurement. This noise level primarily accounts for two sources of ubiquitous noise: the noise induced by the limited capabilities of the mechanotransducers forming the sensing device as well as the signal postprocessing; and the background noise of the fluid flow in which the sensor is placed.…”
Section: Problem Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modelling the pressure sensing after natural or artificial devices (Fan et al 2002;Coombs & Braun 2003;Yang et al 2006), we assume a finite noise-tosignal ratio g in that measurement. This noise level primarily accounts for two sources of ubiquitous noise: the noise induced by the limited capabilities of the mechanotransducers forming the sensing device as well as the signal postprocessing; and the background noise of the fluid flow in which the sensor is placed.…”
Section: Problem Definitionmentioning
confidence: 99%
“…From the robotic standpoint, Fan et al (2002) reported the first design and fabrication of an artificial lateral line flow sensor. Later, Yang et al (2006) reported the first experimentations where such an artificial LLS is used to detect both a dipole and a wake, hence allowing it to mimic the pressure-sensing capabilities of those encountered in nature. Recently, McConney et al (2009) reported yet another biologically inspired design of sensors showcasing more similarities with neuromasts than any other artificial devices before, and enhancing the detection of flow field perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most flow metering devices are based on vanes, hot wire anemometers, ultra sound devices, particle imaging velocimetry, Coriolis force, inductive coupling and vortex shedding [26][27][28][29][30][31]. Most of these systems are not only rather complex and have macroscopic dimensions, but in addition are expensive and/or have a high power consumption.…”
Section: Biomimetic Flow Sensors: State Of the Artmentioning
confidence: 99%
“…Enger et al [21] discovered that Lepomis macrochirus only reacts strongly to balls with vibration frequency below 10 Hz in a dark environment. Furthermore, Yang et al [22] used surface micromachining to manufacture a set of miniaturized hot wire speed sensors (HWAs) to perform dipole source positioning and hydrodynamic wake monitoring. Chen et al [23] developed an ALLS for hydrodynamic object tracking whereas the developed system is yet to be used in practice.…”
Section: Related Workmentioning
confidence: 99%